염화칼슘에 의한 스트로브잣나무의 생장 및 생리반응 - 제선미; Je Sun-mi; 김선희; Kim Sun-hee (한국조경학회지, 2017)
이 연구는 염화칼슘이 스트로브잣나무(Pinus strobus)의 생장 및 생리반응에 미치는 영향과 그 중 염화칼슘에 민감하게 반응하는 변수를 알아보고자 실시되었다. 이를 위해 염화칼슘에 처리에 대한 스트로브잣나무의 가시적 피해, 근원경 생장, 식물체 내 수분함수량, 엽록소함량과 구성, 광계Ⅱ의 최대 활성, 전자전달율의 변화를 분석하였다. 염화칼슘 처리는 개엽하기 전에 염화칼슘 0.5, 1.0, 3.0% 수용액을 근권부에 관수하였다. 염화칼슘 처리에 의한 가시적 피해로 잎의 갈변과 탈락, 잎 마름이 나타났으며, 이러한 피해 양상은 염화칼슘 농도가 높고, 처리 기간이 길어질수록 가중되어 나타났다. 근원경(밑둥지름) 생장량 그리고 잎의 수분함수량의 감소는 염화칼슘 1.0%와 3.0% 처리에서 유의하게 나타났다. 광색소인 총엽록소함량, 광계Ⅱ의 최대 활성, 전자전달율은 염화칼슘 3.0% 처리에서 대조구 대비 유의한 감소를 보였다. 결론적으로 염화칼슘 처리는 엽 내 수분상태에 영향을 주었고, 광수확 능력과 광화학반응 능력의 감소를 초래하였다. 또한, 염화칼슘 농도와 생장 및 생리반응 변수들 간의 상호 연관성을 분석한 결과, 잎의 수분함수량과 엽록소 a와 b의 비율의 회귀식 결정계수가 상대적으로 높아, 스트로브잣나무의 염화칼슘 피해 수준에 민감하게 반응하는 변수로 나타났다. The present study aimed to investigate the effect of calcium chloride(CaCl 2 ) on the growth and physiological responses of Pinus strobus and the variables that are sensitive to CaCl 2 . Thus, changes in the visible damage, growth of root collar diameter, plant water content, chlorophyll content and composition, maximum PSⅡ photochemical efficiency, and electron transport rate of P. strobus was analyzed in relation to treatment witih CaCl 2 . A CaCl 2 solution(0.5, 1.0 and 3.0%) was applied in the root zone before leaf unfolding. Leaf browning, defoliation, and drying were observed with CaCl 2 application and this pattern was aggravated as the CaCl 2 concentration increased and the treatment period became longer. The decrease of growth in root collar diameter and height and leaf water content were observed at CaCl 2 1.0% and 3.0%. The total chlorophyll content indicated that photopigment, PSⅡ photochemical efficiency and electron transport rate significantly decreased at CaCl 2 3.0%. In conclusion, CaCl 2 affected leaf water content and led to a decrease of capability in light harvesting and photochemical responses. Also, as a result of the correlation between calcium chloride concentration and growth and physiological response parameters, it was found that the leaf moisture content and the ratio of chlorophyll a and b reflect the damage level of calcium chloride sensitively because their coefficient of determinations were relatively high.